Bilateral lung transplantation for pulmonary artery aneurysm with severe pulmonary hypertension: An evolution or a revolution?. Issue 8 (16th May 2021) - Jacob, Samuel; Pham, Anthony N.; Sareyyupoglu, Basar; Pham, Si M.
Abstract: The surgical treatment of pulmonary hypertension (PH), with or without pulmonary artery aneurysm, has evolved during the last 40 years from heart–lung transplants to bilateral lung transplants as the treatment of choice for PH patients with preserved right and left ventricular function and without complex cardiac abnomalies.